Evaluation of measles vaccination coverage in Lincang City, Yunnan Province, China - Xiaotong Yang; Tingting Tang; Zhikang Yang; Lu Liu; Shuyi Yuan; Tai Zhang (Human Vaccines & Immunotherapeutics, 2021)
Background: Lincang City in Yunnan Province on the China-Myanmar border, has reached the World Health Organization recommended coverage (95%) for measles-containing vaccine (MCV), but measles outbreaks still occur. We conducted a survey in Lincang City to determine the measles vaccination status of children on the China–Myanmar border. Methods: We used multistage sampling among children aged 8–83 months. Information on measles vaccination status was obtained from the child’s vaccination certificate, and serum samples were tested using commercially available ELISA kits. Results: A total of 938 children were surveyed. The vaccination coverage rate was 98.9% (95% CI: 98.2–99.6%) for measles–containing vaccine dose 1 (MCV1), and 95.8% (95% CI:94.9–96.7%) for measles–containing vaccine dose 2 (MCV2). The timely vaccination coverage rate was 52.0% (95% CI:48.8–55.2%) for MCV1, and 74.1% (95% CI: 82.9–89.0%) for MCV2. The timely-and–complete vaccination coverage rate was 41.0% (95% CI: 36.7–45.3%). The median delay period was 33 (95% CI: 27–39) days for MCV1, and 196 (95% CI: 146–246) days for MCV2. The seropositivity rate in children aged less than 7 years was 94.0% (95% CI: 92.5–95.5%) with a geometric mean titer of 1210.1 mIU/mL. Conclusions: The MCV coverage was high, but timely and timely-and-complete vaccination coverage were low and insufficient to prevent measles outbreaks. It is necessary to add the timely and timely-and-complete vaccination coverage as indicators of vaccination to provide a more complete picture of measles immunization status.